Responsibility and Organization Science: Integrating Micro and Macro Perspectives - Aguilera, Ruth V.; Waldman, David A.; Siegel, Donald S. (Organization Science, 2022)
Responsibility is an important issue in organizations and society. Employees, managers, and owners can behave responsibly in the workplace and beyond. In addition, these individuals can be influenced by the propensity of the organization to behave responsibly. Organizations can pursue strategies that take into account responsibility at the product, firm, industry, and societal levels. This virtual special issue examines 19 articles published in Organization Science that consider responsibility at multiple levels of analysis. An important theme that emerges is that although some studies have crossed levels of analysis, future research would benefit from cross-level or more meso-based approaches.